Pemasaran Produk Secara Online dan Pelatihan Akuntansi untuk Efektifitas Pengelolaan Usaha - Djuharni, Darti; Sonhaji, Sonhaji; Mauludin, Hanif; Prasetyo, Irawan Budi; Djafri, Taufik; Sugiharto, Didik Priyo (STIE Malangkucecwara, 2024)
The purpose of this article is to open the insights and knowledge and skills of MSME actors in the Blimbing area of Malang City, East Java. Activities are carried out in the form of lectures and discussions, as well as assistance related to the use of digital marketing. In addition, the discussion continued with the topic of the importance of making financial records for MSMEs. The results of this activity show that most participants already know the existence of digital marketing, but not all have used it. Those who have not used it because they do not understand and master internet technology. On the other hand, the results of this activity also show that most MSME actors have not made records of their business activities. This is because they consider the record not too important, what is important for them is that the business runs smoothly and they benefit from the results of the business called profit (profit).